Priming of C-Glycoside Flavones in Colobanthus Quitensis with Salicylic Acid, Methyl Jasmonate, Pimelic Acid, Suberic Acid, and Azelaic Acid Elicits Antifungal Activity Against Botrytis Cinerea - Zuniga-Navarro, G; Contreras-Arredondo, R (American Chemical Society, 2025)
Colobanthus quitensis, one of only two native angiosperms in Antarctica, produces C-glycosyl flavones with antifungal activity against Botrytis cinerea. In this study, the exogenous application of the elicitors salicylic acid (SA), methyl jasmonate (MeJA), pimelic acid (PA), suberic acid (SuA), and azelaic acid (AzA) was evaluated for its effect on the accumulation of bioactive metabolites in in vitro-cultivated plants. Exposure to these compounds significantly modulated the expression of key genes in the phenylpropanoid and flavonoid pathways, including pal, chs, chi, and fnsII, as well as regulatory genes such as myb12, bhlh, and wrky33, enhancing PAL activity and the accumulation of C-glycosyl flavones including schaftoside, neoschaftoside, saponarin, and swertiajaponin. This priming process improved the antifungal activity of the extracts, with SuA at 75 μM and MeJA at 50 μM were identified as the most effective treatments. The in vitro culture approach enabled the assessment of protected and hard-to-access species without the need for wild harvesting. These results suggest that the exogenous application of elicitors constitutes an efficient strategy to modulate the biosynthesis of specialized metabolites, with implications for the development of biocontrol agents and the improvement of efficiency in sustainable agricultural systems. © 2025 American Chemical Society.